Comparison of Primary Production Using in situ and Satellite-Derived Values at the SEATS Station in the South China Sea - Shih, Yung-Yen; Shiah, Fuh-Kwo; Lai, Chao-Chen; Chou, Wen-Chen; Tai, Jen-Hua; Wu, Yu-Shun; Lai, Cheng-Yang; Ko, Chia-Ying; Hung, Chin-Chang (Frontiers in Marine Science, 2021)
Satellite-based observations of primary production (PP) are broadly used to assess carbon fixation rate of phytoplankton in the global ocean with small spatiotemporal limitations. However, the remote sensing can only reach the ocean surface, the assumption of a PP vertically exponential decrease with increasing depth from the surface to the bottom of euphotic zone may cause a substantial and potential discrepancy between in situ measurements and satellite-based observations of PP. This study compared euphotic zone integrated PP derived from measurements based on ship-based in situ incubation (i.e., PPin situ) and those derived from the satellite-based vertically generalized production model (VGPM; PPVGPM) for the period 2003∼2016 at the South East Asian Time-series Study (SEATS) station. PP values obtained during the NE-monsoon (NEM: Nov∼Mar; PPin situ = 323 ± 134; PPVGPM = 443 ± 142 mg-C m–2 d–1) were ∼2-fold higher than those recorded during the SW-monsoon (SWM: Apr∼Oct; PPin situ = 159 ± 58; PPVGPM = 250 ± 36 mg-C m–2 d–1), regardless of the method used for derivation. The main reason for the higher PP values during the NEM appears to have been a greater abundance of inorganic nutrients were made available by vertical advection. Note that on average, PPin situ estimates were ∼50% lower than PPVGPM estimates, regardless of the monsoon. These discrepancies can be mainly attributed to differences from the euphotic zone depth between satellite-based and in situ measurements. The significantly negative relationship between PP measurements obtained in situ and sea surface temperatures observed throughout this study demonstrates that both methods are effective indicators in estimating PP. Overall, our PPin situ analysis indicates that a warming climate is unfavorable for primary production in low-latitude open ocean ecosystems.